2017
DOI: 10.2298/gensr1702663c
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sugar beet root yield by AMMI analysis

Abstract: Sugar beet cultivars have different responses in various environments, such as different locations, years, mineral nutrition treatments or the combination of these factors, due to genotype × environment interaction. Additive main effect and multiplicative interaction (AMMI) is one of the most commonly used multivariate methods for analysis and visualization of genotype × environment interaction data. The main goals of the present study were to (i) investigate the application of AMMI method in the analysis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Campbell and Kern (1982) and Trimpler et al (2017) concluded that among the numerous significant factors, year effect had the greatest influence on sugar beet production. In the studies of Sklenar et al (2000) and Ćirić et al (2017) G × E interaction was significant, but not the factor with the strongest effect on yield.…”
Section: Discussionmentioning
confidence: 81%
“…Campbell and Kern (1982) and Trimpler et al (2017) concluded that among the numerous significant factors, year effect had the greatest influence on sugar beet production. In the studies of Sklenar et al (2000) and Ćirić et al (2017) G × E interaction was significant, but not the factor with the strongest effect on yield.…”
Section: Discussionmentioning
confidence: 81%